1992
DOI: 10.1089/ard.1992.2.279
|View full text |Cite
|
Sign up to set email alerts
|

9-Aminoellipticine-Derivatized α- and β-Oligodeoxyribonucleotides Targeted to the Cap of β-Globin mRNA: Hybridization to Natural and Engineered mRNA, Inhibition of Translation, and Improved Effect of Tandem Chains

Abstract: We studied the duplex stability and the antimessenger activity of 9-aminoellipticine-5'-functionalized alpha- and beta-anomeric DNA sequences complementary to the first 14 nucleotides of the rabbit beta-globin mRNA. The duplex formed by the beta-conjugate with the natural mRNA target possessed a marginally better stability to that of the duplex formed by the unfunctionalized compound, as measured by the thermal elution. The alpha-conjugate did not anneal to native mRNA, possibly due to the interference of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Maher and Dolnick have shown that the efficiency of translation arrest could be increased if two oligonucleotides were targeted to tandem binding sites (27). Contiguously bound oligonucleotides have also been shown to increase the stability of Oligo/RNA duplexes and to enhance translation inhibition by ellipticine-derivatized oligonucleotides (28). Reynolds et al obtained efficient photoadducts with AMTderivatized l9mer methylphosphonate oligonucleotides targeted to a 440 base-long bcr/abl RNA target, provided they used two additional tandem oligonucleotides to induce the reaction (29).…”
Section: Discussionmentioning
confidence: 99%
“…Maher and Dolnick have shown that the efficiency of translation arrest could be increased if two oligonucleotides were targeted to tandem binding sites (27). Contiguously bound oligonucleotides have also been shown to increase the stability of Oligo/RNA duplexes and to enhance translation inhibition by ellipticine-derivatized oligonucleotides (28). Reynolds et al obtained efficient photoadducts with AMTderivatized l9mer methylphosphonate oligonucleotides targeted to a 440 base-long bcr/abl RNA target, provided they used two additional tandem oligonucleotides to induce the reaction (29).…”
Section: Discussionmentioning
confidence: 99%
“…These oligonucleotides bind to DNA in the major groove in a sequence‐specific manner to form triple helices. TFOs can also be conjugated to a mutagen, such as psoralen, to introduce mutations at the target site (Duval‐Valentin et al , 1992; Porumb et al , 1992, 1996; Xu et al , 2000; Kalish & Glazer, 2005; Shahid et al , 2006). Targeted activation of HBG gene expression has been obtained through psoralen‐TFO‐mediated mutagenesis to the −280 region of the OCT‐1 promoter in murine erythroleukaemia (MEL) cells (Xu et al , 2000).…”
mentioning
confidence: 99%